2021
DOI: 10.1177/15353702211010415
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium-sensing receptor signaling in regulating transepithelial calcium transport

Abstract: The calcium-sensing receptor (CaSR) plays a critical role in sensing extracellular calcium (Ca2+) and signaling to maintain Ca2+ homeostasis. In the parathyroid, the CaSR regulates secretion of parathyroid hormone, which functions to increase extracellular Ca2+ levels. The CaSR is also located in other organs imperative to Ca2+ homeostasis including the kidney and intestine, where it modulates Ca2+ reabsorption and absorption, respectively. In this review, we describe CaSR expression and its function in transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 142 publications
(207 reference statements)
0
9
0
Order By: Relevance
“…The CaSR also has effects outside of the parathyroid gland, with expression in organs such as the brain, kidney, and intestines where it has effects on neuropathological conditions and modulate renal calcium reabsorption and intestinal calcium absorption. 60,[96][97][98][99] It acts to modulate the expression and activity of calcium and phosphate transporters, channels and pores, including tight junction proteins that regulate both paracellular and transcellular calcium (re) absorption across renal and intestinal epitehlia. 59,97,[100][101][102] CaSR activity has also recently been linked to the modulation of CYP27B1 expression in a HEK-293 cell model.…”
Section: Calcium and The Calcium-sensing Receptormentioning
confidence: 99%
See 3 more Smart Citations
“…The CaSR also has effects outside of the parathyroid gland, with expression in organs such as the brain, kidney, and intestines where it has effects on neuropathological conditions and modulate renal calcium reabsorption and intestinal calcium absorption. 60,[96][97][98][99] It acts to modulate the expression and activity of calcium and phosphate transporters, channels and pores, including tight junction proteins that regulate both paracellular and transcellular calcium (re) absorption across renal and intestinal epitehlia. 59,97,[100][101][102] CaSR activity has also recently been linked to the modulation of CYP27B1 expression in a HEK-293 cell model.…”
Section: Calcium and The Calcium-sensing Receptormentioning
confidence: 99%
“…57,58 Calcium ions bind to the extracellular domain of the CaSR, which at high levels activates the receptor, thereby suppressing PTH secretion when the blood calcium concentration is sufficiently high. 59,60…”
Section: Classic Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypomagnesemia in KCS type 2 patients could be attributed to degradation of transcription factors involved in magnesium homeostasis. Tan et al [90] suggested a potential role of FAM111A in regulation of CaSR, since KCS type 2 shares phenotypic characteristics with ADHH-like hypocalcemia and hypoparathyroidism.…”
Section: Kenny-caffey Syndrome Typementioning
confidence: 99%